SOME QUESTIONS ABOUT THE HISTORY OF THE DEVELOPMENT RIGHTS OF LAND OWNERSHIP (Journal of actual problems of jurisprudence, 2019)
In this article was studied some problems of land ownership rights, and suggest ways of improving the existing legislation ofKazakhstan.